Null subject comprehension and production revisited: a look at English and Italian. (Journal of Child Language, 2026)
This study will investigate how children acquire the option to drop the subject of a sentence, or null subjects (e.g. "Tickles me" instead of "He tickles me"). In languages that do not permit null subjects, children produce sentences with null subjects from 1 to 3 years of age. This non-adultlike production has been explained by two main accounts: first, the null subject sentences may accurately reflect the children's linguistic knowledge, that is, a competence account. Alternatively, they may result from immature processing resources, therefore underestimating children's competence, that is, a performance account. We will test the predictions of these accounts by using a central fixation preference procedure and elicited imitation to measure children's comprehension and production, respectively, in monolingual 19- to 28-month-olds acquiring English (a non-null subject language) and Italian (a null subject language). The results will shed light on acquisition across languages, and the features that provide evidence to a learner.